2022
DOI: 10.1002/path.6026
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohypoxia in paraganglioma and pheochromocytoma is associated with an immunosuppressive phenotype

Abstract: Metastatic pheochromocytoma and paraganglioma (PPGL) have poor prognosis and limited therapeutic options. The recent advent of immunotherapies showing remarkable clinical efficacies against various cancer types offers the possibility of novel opportunities also for metastatic PPGL. Most PPGLs are pathogenically linked to inactivating mutations in genes encoding different succinate dehydrogenase (SDH) subunits. This causes activation of the hypoxia‐inducible factor 2 (HIF2)‐mediated transcriptional program in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Hypoxia is related to the immune status of tumour cells. EPAS1 plays a valuable role in predicting the outcome of PD‐L1 treatment 9 . SNP rs34533650 influences EPAS1 expression in an allele‐specific manner, and EPAS1 expression was associated with the infiltration levels of macrophages, 44 suggesting that genetic variants may influence immune infiltration through the expression of EPAS1 gene associated with colorectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hypoxia is related to the immune status of tumour cells. EPAS1 plays a valuable role in predicting the outcome of PD‐L1 treatment 9 . SNP rs34533650 influences EPAS1 expression in an allele‐specific manner, and EPAS1 expression was associated with the infiltration levels of macrophages, 44 suggesting that genetic variants may influence immune infiltration through the expression of EPAS1 gene associated with colorectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…8 Hypoxia activates several adaptive responses, which are mainly mediated by HIF1α and HIF2α. 9 Previous studies suggested that hypoxia-induced changes affect tumour immune microenvironment. 10 Hypoxia-inducible factor (HIF) pathway genes influence the expression of gene in both tumour cells and immune cells and affect tumour progression and treatment response.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations